2023
DOI: 10.3390/jof9070693
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Physiological, Transcriptomic and Metabolomic Reveals Molecular Mechanism of Paraisaria dubia Response to Zn2+ Stress

Abstract: Utilizing mycoremediation is an important direction for managing heavy metal pollution. Zn2+ pollution has gradually become apparent, but there are few reports about its pollution remediation. Here, the Zn2+ remediation potential of Paraisaria dubia, an anamorph of the entomopathogenic fungus Ophiocordyceps gracilis, was explored. There was 60% Zn2+ removed by Paraisaria dubia mycelia from a Zn2+-contaminated medium. To reveal the Zn2+ tolerance mechanism of Paraisaria dubia, transcriptomic and metabolomic wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…17,18 However, up to now, research on Cordyceps spores is very limited, 19 and Cordyceps spores have not been fully exploited like G. lucidum spores, which is related to the difficulty of artificial cultivation of the fruiting bodies of Cordyceps and its low spore yield. Our research team has obtained a large amount of O. gracilis spore powder through liquid fermentation by microcycle conidiation technology, 20 but the active ingredients of the spore powder are still unknown, which limits its application. To date, researchers have paid attention to major bioactive components, such as cordycepin, adenosine, and polysaccharides of cultures, and analysis of the metabolomic differences among mycelia and natural products of Cordyceps.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 However, up to now, research on Cordyceps spores is very limited, 19 and Cordyceps spores have not been fully exploited like G. lucidum spores, which is related to the difficulty of artificial cultivation of the fruiting bodies of Cordyceps and its low spore yield. Our research team has obtained a large amount of O. gracilis spore powder through liquid fermentation by microcycle conidiation technology, 20 but the active ingredients of the spore powder are still unknown, which limits its application. To date, researchers have paid attention to major bioactive components, such as cordycepin, adenosine, and polysaccharides of cultures, and analysis of the metabolomic differences among mycelia and natural products of Cordyceps.…”
Section: Introductionmentioning
confidence: 99%
“…However, polysaccharides from Cordyceps spores are less studied. In our previous studies, large quantities of O. gracilis were obtained in submerged culture via the microcycle conidiation technique [24]. Numerous studies have shown that the functions of polysaccharides are closely linked to their structural characteristics, such as monosaccharide composition, molecular weight (Mw), and chemical linkages [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The first article of this Special Issue addresses the molecular tolerance mechanism of Paraisaria dubia to Zn 2+ stress and the possible application of Paraisaria dubia in the bioremediation of heavy metal pollution [1]. The second article analyzes the ectomycorrhizal communities in a former uranium mine and communities under experimental conditions to improve plants' tolerance to certain abiotic conditions [2].…”
mentioning
confidence: 99%